The political stance of the Alliance of Concerned Citizens for Kemaro Island towards the Development Plan by the Palembang City Government for Kemaro Island. - YUSDIA, NOVIA RUANA (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This reserach is discusses the Political Attitude of AMPPK (The Alliance of CommunityConcerned for Kemaro Island) to the Palembang City Government's Plan for Development inKemaro Island. This study aims to find out how AMPPK's political attitude towards thePalembang City Government plan and how the factors behind AMPPK's political attitudetowards the Palembang City Government's plan in the development of development on KemaroIsland. The main problem in this study is related to the problem of the policy concept planned bythe Palembang City Government is not appropriate and this policy was taken without anycontribution from the relevant parties. The data used in this study are primary data andsecondary data, primary data through direct interviews with informants, while secondary data inthe form of related journal articles. Data was collected through interviews and documentation.The result of this research is to determine the political attitude of AMPPK (KemaroIsland Concerned Society) towards the Palembang City Government plan in developingdevelopment on Kemaro Island which expressly does not support the existence of thedevelopment plan on the grounds that the policy concept planned is not in accordance withexisting historical facts and there is no contribution between the Palembang City Governmentand related parties who have an interest in Kemaro Island.